Paradigma Sistem Kapitalisme Dan Islam Tentang Welfare State - Muhammad Kambali (JES (Jurnal Ekonomi Syariah), 2019)
Welfare state or better known as the term prosperous is a form of actualization of idealism that upholds the values of humanism. It containS a set of ideal ideas on how the state is able to serve its people. Capitalism as a modern economic system, which is first demonstrated by humans, built the concept of the walfere state on the philosophy of laizes fair, which manifested itself in a free market system that uphold the value of free faith liberalism. The state in the capitalist system has a famous role with the term minimal role which in the term Adam Smith is said to be no intervesion. These roles include defense security, enforcement of justice and providing and maintaining certain public facilities and institutions. While the concept of walfere state in Islam is an effort to synergize worldly material interests with the spiritual interests of ukrowiyah. In addition, the concept of the welfare state in Islam is also based on the principles of Tawhid, al-Adl and khilafah. The role of the government in the Islamic conception includes fulfilling basic needs and guaranteeing the achievement of spiritual values. The fundamental difference between the two views of this system lies in the aspect of its philosophical foundation. Keywords: Walfare State, Laizes Fair, Tauhid, al-‘Adl